Mineral and heavy metal variations and contaminations in raw honey of stingless Bees, Heterotrigona itama, from selected geographical areas of origin in Malaysia - Bellericter Binjamin; Mohd IftarJohwan Johny @ Hasbullah; Kimberly Ador; Januarius Gobilik; Clament Fui Seung Chin; Mok Sam Lum; Nurul’azah Mohd Yaakub; Suzan Benedick (Journal of the Nutrition Society of Malaysia, 2024)
Honey contains a complex matrix of different substances consisting of essential minerals, non-nutritive substances, and toxins, often due to environmental sources. The objectives of this study were i) to investigate the variation of mineral and heavy metal content in honey samples of Heterotrigona itama from different geographical origins, and ii) to evaluate the nutritional quality and safety of honey from different floral sources for human consumption. Methods: A total of 75 samples of raw H. itama honey were collected from 11 sites in Sabah, two sites in Sarawak, and two sites in Peninsular Malaysia. The mineral and heavy metal contents of honey were determined in triplicate using inductively coupled plasma mass spectrometry (ICP-MS). Results: There were significant differences in the composition of essential minerals and heavy metals in the honey samples according to geographical origins (p<0.001). All honey samples tested were below the permitted maximum proportion (ML) for cadmium (Cd) and lead (Pb) specified in the Malaysian Food Act 1983 for honey. However, all honey samples exceeded the ML for Pb set by Codex, with samples from bamboo sites having the highest levels for Pb. Conclusion: The composition of minerals and heavy metals in stingless bee honey was influenced by geographical origin. All measured Pb concentrations were above the ML value set by Codex, which raises concerns about possible toxicological risks to human health. Given the toxic nature of Pb in the environment, the measured concentrations emphasise the importance of monitoring Pb in honey from stingless bees.